MACC1-induced migration in tumors: Current state and perspective - Hohmann, Tim; Hohmann, Urszula; Dehghani, Faramarz (Frontiers in Oncology, 2023)
Malignant tumors still are a global, heavy health burden. Many tumor types cannot be treated curatively, underlining the need for new treatment targets. In recent years, MACC1 was identified as a promising biomarker and drug target, as it is promoting tumor migration, initiation, proliferation and others in a multitude of solid cancers. Here, we will summarize the current knowledge about MACC1 induced tumor cell migration with a special focus on the cytoskeletal and adhesive system. In addition, a brief overview of several in vitro models used for analysis of cell migration is given. In this context, we will point to issues with the currently most prevalent models used to study MACC1 dependent migration. Lastly, open questions in MACC1 dependent effects on tumor cell migration will be addressed.